Level of critical thinking and problem solving skills of administrator nurses and nurses who work at private hospitals - (:unkn) unknown (AVES PRESS LTD, 2015)
Purpose: The descriptive study was conducted during September-October 2010 in order to determine critical thinking level and problem solving ability of nurse managers and nurses working at private hospitals. Method: The sample group is formed by 109 nurse managers and 1314 nurses who were available and agreed to take part in the study. Information form including identifying and professional characteristics of nurse managers and nurses, California Critical Thinking Disposition Inventory (CCTDI), and Problem-Solving Inventory (PSI) were used as data collection tools. The data were evaluated with percentage, mean, standard deviation, independent samples test, One-Way ANOVA, Scheffe's test, and Pearson's correlation test. Results: CCTDI mean scores were low for the nurse managers (225.2 +/- 20.9) and for nurses (222.8 +/- 21.4). Mean scores of systematicity sub-scale (27.2 +/- 3.9) and inquisitiveness sub-scale (42.1 +/- 6.1) of CCTDI were observed to be higher in nurses compared to nurse managers. PSI mean scores were determined to be average for nurse managers (102.6 +/- 12.8) and nurses (101.1 +/- 15.6). Mean scores of problem-solving confidence (31.4 +/- 6.7) and approach-avoidance sub-scales (44.5 +/- 7.2) of PSI were higher in nurse managers compared to nurses. Age group, educational status, professional working period, unit worked and working type of nurses affected their CCTDI scores whereas educational status of nurse managers and nurses affected PSI scores with statistical significance (p<0.05). Conclusion: Critical thinking levels of nurse managers and nurses were found to be low based on CCTDI and their problem solving skills were determined to be average based on PSI. In the light of these results, it is recommended to provide internal and external training programs and develop strategies in order to improve critical thinking disposition and problem solving skills.
Keywords: Administrator nurses; critical thinking levels; nurse; problem solving